Ketangguhan Institusi Islam dalam Pelaksanaan Pembelajaran Daring - Mahsusi Mahsusi; Syihaabul Hudaa; Nuryani Nuryani (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2022)
The pandemic started to hit the world in 2019, making the education system unable to run face-to-face as usual. Islam views this pandemic as something to avoid. Therefore, people were demanded to stay at home. The same thing happened in the world of education, especially in the learning system which was previously changed to an online system (blended learning). Teachers anticipated this system by using several existing media, such as: Zoom, Meet, Google Classroom, and other applications. The purpose of writing this article was to discuss Islamic institutions in dealing with a pandemic in the realm of education for the common good. This study was included in the type of descriptive qualitative study using mixed methods with a questionnaire instrument basis to obtain data and description for data analysis. The data was a questionnaire form and several arguments used as the basis for the analysis in this study. The data was correlated with the education system in the midst of the Covid-19 pandemic by observing t the final grades of the Indonesian language course for non-language students at UIN Syarif Hidayatullah Jakarta. The results show that Islamic law recommends the best efforts to deal with a pandemic. Although UIN Jakarta as an Islamic institution does not seem ready, it is still able to prove resilience in various ways. One of which is optimizing the use of the Academic Information System (AIS) and subscribing to premium zoom for all lecturers. The results of student learning tests using the online method are classified as good from the specified targets. However, significant differences in scores still occur and are quite visible between face-to-face learning and online learning systems.